Investigation of antioxidant and antimicrobial properties of biosurfactants derived from Lactobacillus plantarum, Lactobacillus pentosus and Lactobacillus casei - Behzad Akbarzadeh Najar; Peiman Ariaii; Mahro Esmaeili; Roya Bagheri (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2023)
Biosurfactants are amphipathic compounds that are produced by many microorganisms and show a wide range of biological activities due to their unique characteristics. This study aimed to determine the antioxidant and antimicrobial potential of the biosurfactants isolated from Lactobacillus plantarum, Lactobacillus pentosus, and Lactobacillus casei. The antioxidant activity of biosurfactant was evaluated in vitro conditions using the ability to inhibit 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and hydroxyl free radicals and antimicrobial activities using the diffusion method in agar wells against pathogenic bacteria. The results showed that the inhibitory activity of DPPH and hydroxyl of biosurfactants at a concentration of 5 mg/ml was 78.51-81.99% and 69.51-71.56%, respectively, and the highest antioxidant activity was related to Lactobacillus plantarum (P<0.05). The results of inhibiting microbial growth showed that all biosurfactants had high antimicrobial activity and the antimicrobial activity against Staphylococcus aureus (gram-positive) was higher than other bacteria (gram-negative). No significant difference was observed among different biosurfactants. It seems that biosurfactants obtained from lactobacilli can be used as natural antioxidants and antimicrobials in the food and pharmaceutical industries.